Peramalan Kemiskinan di Kabupaten Banyumas Menggunakan Regresi Nonparametrik dengan Pendekatan Kernel Nadaraya Watson Adjusted - Novita Eka Chandra; Melda Juliza; Muhammad Hafidh Nashrullah (Mathematics Department, Faculty of Sciences and Technology Unisda Lamongan, 2025)
Poverty is a serious challenge faced by the Banyumas Regency Government. Although the poverty rate in this region has shown a declining trend for more than a decade, the pattern of decline has not been linear. This study utilizes time series data representing the percentage of the poor population in Banyumas Regency from 2003 to 2024. This research primarily seeks to forecast the poverty rate in 2030 and to differentiate between the performance of two kernel functions, Gaussian and Epanechnikov, which are applied in nonparametric regression using the adjusted Nadaraya-Watson kernel approach. Analysis results suggest that the model performs best when the bandwidth is set at its optimal value of 0,538909 using the Epanechnikov kernel function. Based on the forecast, the poverty rate in 2030 is estimated to be 12,87%. This result indicates the need for well-planned strategies and policies by the Banyumas Regency Government to reduce the poverty rate over the next six years.